2021
DOI: 10.1080/23299460.2021.1904755
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the readiness of publicly funded researchers to practice responsible research and innovation in digital agriculture

Abstract: Responsible Research and Innovation (RRI) has been highlighted as necessary for the governance of digital agriculture. The current study explores the readiness of publicly funded researchers in Ireland to engage in RRI activities in digital agriculture. In-depth one-to-one interviews were carried out with 15 scientists and research funders to understand how perceived emergent risks in digital agriculture are being addressed and to reflect on the extent to which responses align with RRI principles. Thematic Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…With the rapid advancement of digital technologies in rural communities and industries, social researchers have started developing approaches aimed at guiding agri-food transitions in socially beneficial and equitable directions (Eastwood et al, 2019(Eastwood et al, , 2021Fielke et al, 2020;Jakku et al, 2018Jakku et al, , 2022Regan, 2019Regan, , 2021Robinson et al, 2014;Rotz et al, 2019). Recognition of this work is critical for realising the promise of investment in digital agricultural transformation, with processes grounded in awareness of the interrelated change processes facing rural communities.…”
Section: Rural Social Research and Responsible Digital Agtechmentioning
confidence: 99%
“…With the rapid advancement of digital technologies in rural communities and industries, social researchers have started developing approaches aimed at guiding agri-food transitions in socially beneficial and equitable directions (Eastwood et al, 2019(Eastwood et al, , 2021Fielke et al, 2020;Jakku et al, 2018Jakku et al, , 2022Regan, 2019Regan, , 2021Robinson et al, 2014;Rotz et al, 2019). Recognition of this work is critical for realising the promise of investment in digital agricultural transformation, with processes grounded in awareness of the interrelated change processes facing rural communities.…”
Section: Rural Social Research and Responsible Digital Agtechmentioning
confidence: 99%
“…In her study, Bronson (2019) found that different actors have different understandings of digitalisation, and adapt their practices accordingly. Regan (2021) examined the levels of alignment between the practices used by researchers and the principles of RRI, uncovering encouraging findings concerning the practice of inclusion. Others, not directly following the RRI research tradition, also offer insights into how actors' practices catalyse agricultural digitalisation.…”
Section: Digitalising Responsiblymentioning
confidence: 99%
“…It also opens‐up questions about who is responsible for the inclusion of marginalized groups in the co‐design of new AgTech, suggesting the need for discovering ways to ensure inclusion is a responsibility recognized by all researchers engaged in co‐design, not only social scientists. We believe having open discussions about response‐able mattering could support researchers engaged in co‐design to develop the skills and mindsets necessary to practice more responsible research and innovation (see Regan 2021).…”
Section: Response‐able (Re)configurationsmentioning
confidence: 99%